A new species of Macrocentrus (Hymenoptera: Braconidae) parasitizing larva of Dioryctria pryeri (Lepidoptera: Pyralidae) - Song, Li-Wen; Cao, Liang-Ming; Li, Xing-Peng; Yang, Zhong-Qi; Chen, Yue-Qu (Zootaxa, 2017)
Macrocentrus pryeri Yang, Song & Cao, sp. nov. (Hymenoptera: Braconidae), a gregarious larval endo-parasitoid of Dioryctria pryeri Ragonot (Lepidoptera: Pyralidae), is described and illustrated. The hosts is serious pest of the cone, seed and shoot of Pinus koraiensis Sieb. et Zucc., a dominant forest tree species in northeastern China. The parasitoid has potential as a biocontrol agent for the pest as an average parasitism rate of 27.5% has been observed (Maximum 40%), and, on average, 40.4 parasitoid adults (range 29–48) emerge from a single host with female:male ratio of 1.9:1 (Maximum 2.8:1). Detailed photographs of the key characters of the female and male of the new species are provided.